ANALYSIS OF PERCEPTION OF PATIENT CARE PATIENTS PHYSIOTHERAPY LOYALTY - novan asnandra (HUMAN CARE JOURNAL, 2018)
Loyalty becomes a real form on the willingness patients for reuse, which has a strength and a positive attitude. Physiotherapy services is one form of health services needed by the community. The purpose of this study to analyze the patient's perception of physiotherapy outpatient unit of physiotherapy services to the loyalty of patients at Ibnu Sina Islamic Hospital Bukittinggi. The research method with a combination of research methods(mixed method),with the design of sequential explanatory design. Samples are old patient who came to Physiotherapy Unit, the sampling technique accidental sampling (quantitative) and purposive sampling (qualitative) as many as 110 patients a long time and the number of informants 3 patients. Data analysis usingtest, Chi Squareand qualitative analysis. Based on the results, unfavorable patient's perception regarding tangible (60.9%),reliability (80%),responsivenes (92.7%),assurance (88.2%), except empaty (82.7%), with the lack of loyalty patients (73.6%) in the physiotherapy unit. The absence of a relationship between the patient's perception of physiotherapy tangible services,reliability, responsivenes,assurance,and empathy,loyalty patient in the hospital. Islam Ibnu Sina Bukittinggi. Interviews, observation and document study research shows perceptions poorly to 4 variable tangible, reliability, responsivenes, assurance except empathy variable perception of good, judging from the many shortcomings in terms of infrastructure and the patient is less loyal and need factors are factors that influence loyalty patient in an outpatient physiotherapy unit. It is expected for the Hospital in order to further optimize both in terms of facilities and infrastructure, and increase the number of officers physiotherapy unit.Keywords: Loyalty; Perception; Physiotherapy services